BELAS KASIH RAJA: TINJAUAN TEOLOGIS-NARATIF TERHADAP ANUGERAH DALAM KISAH MEFIBOSET (2 SAMUEL 9:1–13) - siagian, sapta baralaska utama (Jurnal Teologi Biblika, 2026)
The story of Mephibosheth in 2 Samuel 9:1–13 is one of the important narratives in the Old Testament that represents the concept of love (ḥesed) as the foundation of the covenant relationship between God and man. This study aims to analyze the theological significance of King David's actions towards Mephibosheth and its relevance to the understanding of grace in biblical theology. This study uses a descriptive qualitative approach through literature studies with the narrative exegesis method of biblical texts and Old Testament theological literature. The results of the study show that David's actions reflect the three main dimensions of grace, namely love that takes the initiative to seek, love that raises dignity, and love that restores identity. Mephibosheth's transformation from Lo-Debar to the king's table illustrates the transition from alienation to acceptance in covenant relationships. This finding confirms that grace is not based on human worthiness, but rather on the faithfulness of the giver. Theologically, this narrative serves as a typology of the Gospel that describes the restoration of the relationship between God and man. The implications of this study show that the church today is called to develop inclusive, restorative, and grace-centered ministry as a form of witness of faith in society.